MANDIBULAR RADIOGRAPHIC ANALYSIS FOR GENDER DETERMINATION OF DOWN SYNDROME SUFFERERS - Rendra Chriestedy Prasetya; Amandia Dewi Permana Shita; Nadie Fatimatuzzahro; Nuzulul Hikmah; Hafiedz Maulana; Indonesia Koes Wijayaningrat; Adinda Febriyanti; Dwi Kartika Apriyono (Journal of Vocational Health Studies, 2025)
Background: Natural disasters frequently occur in Indonesia, creating a need for effective victim identification. Gender identification is a crucial initial step, as it can narrow the search space by 50% during individual identification. The corpus and ramus mandible are an organ that plays an important role in gender prediction with a high predictive accuracy. However, the Down syndrome mandibular size is different from that of normal people. Purpose: To analyze the difference in corpus length and total height of the mandibular ramus between individuals with down syndrome and those without, as a step to gender determination. Method: This observational cross-sectional study involved 12 individuals with down syndrome and 12 individuals without, aged 10 – 17 years. The mandibular corpus length was measured through panoramic radiography from the gonion to the menton point. The mandibular ramus was measured from the apex of the condyle to the gonion point using the Clinicview application. Data were analyzed using the T-test with SPSS Ver. 26 software. Result: The length of the mandibular corpus differs significantly (p-value = 0.000) between Down syndrome with normal people. The length of the mandibular corpus in down syndrome does not differ significantly (p-value > 0.000) between males and females. The total height of the mandibular ramus does not differ significantly between down syndrome and non-down syndrome groups, both in males and females. Conclusion: The corpus length and the mandibular ramus's total height cannot be used as indicators of gender determination in down syndrome.